Nanofibrous paper for fingerprint mapping and the inspiration in microimprinting assisted precious patterning. (December 2020) - Feng, Pingping; Pan, Nan; Song, Botao
Abstract: A fingerprint is one of the unique and authoritative information for personal identification; however, the entire three levels of ridge patterns, especially clear sweat pore information, can not be facilely obtained by the current methodologies. Herein, after careful investigation on the physiological structure of a fingertip, we describe the use of a super-soft and water-sensitive poly (vinyl alcohol) (PVA) nanopaper for mapping the entire three levels of ridge patterns. Thanks to the unique softness, the detailed ridge/furrow patterns (level 1 and 2) can be copied onto the nanopaper, while the water-sensitive feature enables an in-situ fast and selective dissolution of nanopaper by a tiny amount of water secreted through sweat pores to map clear sweat pore patterns (level 3). Further, inspired by the fingerprint pressing process, we combine electrospinning with microimprinting approach to create nanofibrous materials with controllable patterns (single, dual, and complex patterns). The proposed method exhibits superior features than currently reported patterning approaches, such as high throughput, low cost, and high efficiency. Finally, we demonstrate the potential application of the patterned PVA nanopaper for ultrafast water-sensing anti-counterfeiting. Highlights: A super-soft and water-sensitive PVA nanopaper is fabricated by electrospinning. PVA nanopaper can map the entire three levels of ridge patterns of fingerprint. Diverse patterns are created on PVA nanopaper by electrospinning/microimprinting.